Evaluation of stress intensity factor of multiple inclined cracks under biaxial loading - A.K. Chaudhary; R. K. Bhagat; V. K. Singh; P. C. Gope (Fracture and Structural Integrity)
A finite rectangular plate of unit thickness with two inclined cracks (parallel and non parallel) under biaxial mixed mode condition are modelled using finite element method. The finite element method is used for determination of stress intensity factors by ANYSIS software. Effects of crack inclination angle on stress intensity factors for two parallel and non parallel cracks are investigated. The significant effects of different crack inclination parameters on stress intensity factors are seen for lower and upper crack in two inclined crack. The present method is validated by comparing the results from available experimental data obtained by photo elastic method in same condition.